Meta-heurísticas para o problema de planejamento de expansão da rede de transmissão de energia elétrica considerando restrições de segurança - Lemos, Robinson Alves [UNESP] (2015)
This work deals with the energy network transmission expansion planning problem (TEP) and uses two variations of the CC model on the static planning horizon: with N-1 security constraints (STEPS) and the usual formulation, without security constraints (STEP). The meta-heuristics tabu search (TS), GRASP and iterated local search (ILS) were implemented using the framework ParadisEO and the parameters tunning were made with the aid of paramILS. The algorithms were tested in 42 test systems divided into 6 groups: Garver 6 bars (4 test systems), IEEE 24 bars (10 test systems), 46 South Brazilian bars (4 test systems), Brazilian Southeast 79 bars (4 test systems), Brazilian Northeast 87 bars (8 test systems) and Colombian 93 bars (12 test systems). The tests showed the viability of ParadisEO framework to implement meta-heuristics for the TEP problem. In addition, a large benchmark for use in future STEP and SSTEP works was created.